Away from Feminist Radicalism: A New Reading of Calixthe Beyala’s Maman a un amant and La petite fille du réverbère - Ogundokun, Sikiru; KUFISILE, Peter (Al-Adab Journal, 2024)
Calixthe Beyala’s creative works and public comments on her artistic productions and her life in general have enjoyed a remarkable attention without any doubt. However, there is a particular aspect of her literary creativity begging for attention. This study, therefore, is set to investigate Beyala’s religious disposition with a view to establishing the fact that African women do not only reject being restricted to the kitchen but also demonstrate that they should be considered when it comes to the matter of exercising their faith. The two novels selected for this study are Calixthe Beyala’s Mama a un amant and La petite fille du réverbère. They can be translated as Mama has a Lover and The little girl under the street lamp. Adopting sociological conceptual framework, data are analyzed using the French explication de texte which can be interpreted as the close reading technique or content analysis of a text, verbal or non-verbal. Findings from the study suggest that the new generation of African female writers focuses on an attempt to establish and reconnect womenfolk with their most fundamental human rights through artistic designs and their creative writings. Besides being a means of socialization, religion is a ritualistic act of worship, and it reflects a significant part of a people’s way of life. The study, however, concludes that there is a need for check and balance between the idea of masculinity and the concept of feminism to curtail the excesses there-in for the progress of human societies.